Enhancing Wheat Crop Productivity in Acidic Soils of Tsegede Highlands, Northern Ethiopia: A Study on the Effects of Liming Materials and N-P Fertilizers - Hadera, Abreha Kidanemariam (Soil Acidity Characterization and Effects of Liming and Chemical Fertilization on Microbial Growth, Nutrient Uptake and Yield of Wheat (Triticum aestivum L.): The Case of Acidic Soils in Tsegede District, Northern Ethiopia, Edition 1, 2024)
Ethiopia is one of the largest wheat-producing countries in sub-Saharan Africa. Soil acidity is one of the serious problems constraining wheat crop production in small-scale farmers of the central, western, and southern highlands of Ethiopia where precipitation is high enough to leach down soluble salts. A greenhouse experiment was carried out on acidic soils collected from the Tsegede highlands of northern Ethiopia, where wheat production is severely constrained by soil acidity, to evaluate wheat crop response to the applications of liming materials (Wukro lime and Sheba lime) and N and P fertilizers. Three lime sources (without lime, Wukro lime, and Sheba lime) and four N and P fertilizers (without N and P, recommended N, recommended P, and recommended N + recommended P) were arranged in a factorial experiment using a randomized complete block design with four replications. The results indicated that yield and yield attributes of wheat showed significant (P \(\le\) 0.01) response to the main effects of lime and fertilizer applications. Similarly, the fertilizer by lime interaction effect was significantly (P \(\le\) 0.05) different in grain yield, total biomass, and N and P uptakes. The soils that received only recommended N + recommended P fertilizers (NP), Wukro lime and Sheba lime showed significant grain yield increments by about 78, 76, and 96% over the control, respectively. However, the applications of NP + Wukro lime and NP + Sheba lime augmented grain yield by 239 and 233%, respectively, over the control plot. Likewise, N uptakes were enhanced by about 66, 80 and 81% and P uptakes by 93, 91 and 93% in the soils that received only NP, Wukro lime, and Sheba lime over the control while the application of NP + Wukro lime and NP + Sheba lime increased N uptakes by 241 and 237% and P uptakes by 451 and 471% over the control, in that order. The highest agronomic efficiency and apparent recovery efficiency were also recorded in the soils treated with Wukro and Sheba limes along with only recommended P and NP fertilizers, respectively. Hence, a combined application of adjusted lime rate and NP fertilizers is recommended to achieve sustainable wheat crop production on acidic soils of the Tsegede highlands. Further field studies on heavy application of P fertilizer intended to determine the optimum rate that must be applied to reclaim soil acidity and combined with N fertilizer are essential.